2019
DOI: 10.1016/j.jaad.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Topical glycopyrronium tosylate for the treatment of primary axillary hyperhidrosis: Results from the ATMOS-1 and ATMOS-2 phase 3 randomized controlled trials

Abstract: GT applied topically on a daily basis over 4 weeks reduced the severity of sweating as measured by ASDD-Item 2, reduced sweat production as measured gravimetrically, and was generally well tolerated in patients with primary axillary hyperhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
91
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 19 publications
14
91
0
2
Order By: Relevance
“…These subgroup data are consistent with previous findings of individual and pooled ATMOS‐1 and ATMOS‐2 data showing that GT improved disease symptoms, severity, and quality of life vs vehicle . ASDD/ASDD‐C Item 2 responder rates were nearly identical among GT‐treated pediatric and older subgroup patients.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These subgroup data are consistent with previous findings of individual and pooled ATMOS‐1 and ATMOS‐2 data showing that GT improved disease symptoms, severity, and quality of life vs vehicle . ASDD/ASDD‐C Item 2 responder rates were nearly identical among GT‐treated pediatric and older subgroup patients.…”
Section: Discussionsupporting
confidence: 89%
“…Identical excipients were included in the vehicle comparator of the ATMOS trials to account for any potential effect due to a compound other than active drug. Though a vehicle effect was observed in these trials, GT‐treated patients had a significantly greater response than that observed with vehicle …”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations